Analysis of Halal Production Process in PGC Catering Sidoarjo - Rima Azara; Fitriyah Nur Indahsari; Rahmah Utami Budiandari (Journal of Halal Lifestyle and Sustainability, 2025)
Halal is often associated with food and beverages permissible for consumption, governed by regulations that ensure products do not contain prohibited elements. Catering is a food processing industry that must obtain halal certification. PGC Catering, established in Sidoarjo since 2016. This research aims to analyze critical points in the PGC Catering processing process. Methods used include interviews with the catering owner, observations, data analysis, and literature review. The results indicate that the selection of halal raw materials, along with their storage and processing, significantly impacts the halal status of the products produced. Additionally, the packaging and distribution processes are conducted with a focus on cleanliness and safety. In conclusion, PGC Catering meets the halal standards set by certification bodies, thereby enhancing Muslim consumer trust in the products offered